1956
DOI: 10.1037/h0083660
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in pain thresholds.

Abstract: IN THE PAST couple of decades a variety of studies dealing with pain thresholds have been reported. Some of these studies have been concerned with thermal-pain thresholds, others with electrical-or pressurepain thresholds. Some investigators have used uninstructed and naive subjects, while others have used subjects who were both sophisticated and specifically instructed. Except for a series of studies (5) in which a small number (three) of highly sophisticated and instructed subjects was used, the most strikin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1970
1970
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 13 publications
2
21
0
1
Order By: Relevance
“…One resolution is to argue that the signal detection analysis offers the most accurate picture of the threshold process (see Green & Swets, 1966;Massaro, 1975;Swets, 1961) and that the sequential model is likely to be wrong. This conclusion would also be consistent with earlier data showing that the same factors affect emotional reactions at both pain and tolerance thresholds (Clark & Bindra, 1956). A second resolution would be to argue that the procedures used in the signal detection experiment, which presents a large number of stimuli in series and asks the subject to focus on the sensory components rather than seeing how much pain he can tolerate, cause an artificial separation of sensation and emotion, and that under real-life conditions involving clinical pain, sensation and emotional reaction components are integral and correlated (Garner, 1974).…”
supporting
confidence: 92%
“…One resolution is to argue that the signal detection analysis offers the most accurate picture of the threshold process (see Green & Swets, 1966;Massaro, 1975;Swets, 1961) and that the sequential model is likely to be wrong. This conclusion would also be consistent with earlier data showing that the same factors affect emotional reactions at both pain and tolerance thresholds (Clark & Bindra, 1956). A second resolution would be to argue that the procedures used in the signal detection experiment, which presents a large number of stimuli in series and asks the subject to focus on the sensory components rather than seeing how much pain he can tolerate, cause an artificial separation of sensation and emotion, and that under real-life conditions involving clinical pain, sensation and emotional reaction components are integral and correlated (Garner, 1974).…”
supporting
confidence: 92%
“…The rationale of the present experiment is based upon a determination of psychological and psychophysical rules in subjects who differ in the degree to which they report the same shock intensities as eliciting pain. Variation between people in such measures as pain threshold (the stimulus magnitude for which a subject first reports feeling pain) and tolerance (the most extreme stimulus magnitude that the subject is willing or able to experience)is typically quite high (seeClark & Bindra, 1956;Clausen & King, 1950;Dillon, 1968;Notermans & Tophof, 1967; …”
Section: Methodsmentioning
confidence: 99%
“…In 1934, Libman (4) reported that pressure applied to the mastoid bone in the direction of the styloid process produces ''marked'' pain in 60-70% of his human patients, but no or little pain in 30-40%. Subsequent investigations over the next few decades with more quantitative methodology confirmed the presence of large individual differences in threshold sensitivity and tolerance to noxious pressure (5)(6)(7)(8), heat (7,9,10), and electrical current (7,11) applied to cutaneous tissues, and tolerance to visceral (6) and deep muscle (9,10) pain. Impressive individual differences in sensitivity to opioid analgesics were also documented during this period, typified by Lasagna and Beecher (12) observing a ''success rate'' of only 65% of the standard clinical dose of morphine, 10 mg (see also ref.…”
Section: The Scope Of Individual Variability To Pain and Analgesiamentioning
confidence: 99%